Developing a Health Information Technology Systems Matrix: A Qualitative Participatory Approach - Haun, Jolie N (J Med Internet Res, 2016)
BACKGROUND: The US Department of Veterans Affairs (VA) has developed various health information technology (HIT) resources to provide accessible veteran-centered health care. Currently, the VA is undergoing a major reorganization of VA HIT to develop a fully integrated system to meet consumer needs. Although extensive system documentation exists for various VA HIT systems, a more centralized and integrated perspective with clear documentation is needed in order to support effective analysis, strategy, planning, and use. Such a tool would enable a novel view of what is currently available and support identifying and effectively capturing the consumer’s vision for the future. OBJECTIVE: The objective of this study was to develop the VA HIT Systems Matrix, a novel tool designed to describe the existing VA HIT system and identify consumers’ vision for the future of an integrated VA HIT system. METHODS: This study utilized an expert panel and veteran informant focus groups with self-administered surveys. The study employed participatory research methods to define the current system and understand how stakeholders and veterans envision the future of VA HIT and interface design (eg, look, feel, and function). Directed content analysis was used to analyze focus group data. RESULTS: The HIT Systems Matrix was developed with input from 47 veterans, an informal caregiver, and an expert panel to provide a descriptive inventory of existing and emerging VA HIT in four worksheets: (1) access and function, (2) benefits and barriers, (3) system preferences, and (4) tasks. Within each worksheet is a two-axis inventory. The VA’s existing and emerging HIT platforms (eg, My HealtheVet, Mobile Health, VetLink Kiosks, Telehealth), My HealtheVet features (eg, Blue Button, secure messaging, appointment reminders, prescription refill, vet library, spotlight, vitals tracker), and non-VA platforms (eg, phone/mobile phone, texting, non-VA mobile apps, non-VA mobile electronic devices, non-VA websites) are organized by row. Columns are titled with thematic and functional domains (eg, access, function, benefits, barriers, authentication, delegation, user tasks). Cells for each sheet include descriptions and details that reflect factors relevant to domains and the topic of each worksheet. CONCLUSIONS: This study provides documentation of the current VA HIT system and efforts for consumers’ vision of an integrated system redesign. The HIT Systems Matrix provides a consumer preference blueprint to inform the current VA HIT system and the vision for future development to integrate electronic resources within VA and beyond with non-VA resources. The data presented in the HIT Systems Matrix are relevant for VA administrators and developers as well as other large health care organizations seeking to document and organize their consumer-facing HIT resources.